The way forward - Bouis, Howarth E.; Saltzman, Amy; Low, J. W.; Ball, Anna-Marie; Covic, Namukolo (African Journal of Food, Agriculture, Nutrition and Development, 2017)
Biofortification has made more rapid progress in Africa than in Asia or Latin America. Thus, Africa provides an important first view into learning how to implement biofortification successfully, and its potential to improve nutrition and public health. The preceding articles have summarized the evidence available for biofortification, particularly in the African context. Over the last 15 years, biofortification research demonstrated broadly that:  Conventional breeding can add extra nutrients in the crops without reducing yields.  When consumed, the increase in nutrient levels can make a measurable and significant impact on human nutrition.  Farmers are willing to grow biofortified crops and consumers to eat them. While there remains more to be learned, the biofortification intervention should now be scaled up. To reach full potential, a global effort, with many partners – governments, researchers, private sector actors, civil society organizations, and farmers – is now required to bring more crops to more farmers, changing more lives.